Perfectly reasonable deviations from the beaten track : the letters of Richard P. Feynman - Feynman, Richard P. (Richard Phillips), 1918-1988 (Basic Books, 2005)
One of the towering figures of twentieth-century science, Richard Feynman possessed a curiosity that was the stuff of legend. Even before he won the Nobel Prize in 1965, his unorthodox and spellbinding lectures on physics secured his reputation amongst students and seekers around the world. It was his outsized love for life, however, that earned him the status of an American cultural icon--here was an extraordinary intellect devoted to the proposition that the thrill of discovery was matched only by the joy of communicating it to others. In this career-spanning collection of letters, many published here for the first time, we are able to see this side of Feynman like never before. As edited and annotated by his daughter, Michelle, these letters not only allow us to better grasp the how and why of Feynman's enduring appeal, but also to see the virtues of an inquiring eye in spectacular fashion. The result is a wonderful de facto guide to life, an eloquent testimony to the human quest for knowledge at all levels.